Spatial Epidemiology of Plasmodium vivax, Afghanistan - Brooker, Simon (Centers for Disease Control and Prevention, 2006)
Plasmodium vivax is endemic to many areas of Afghanistan. Geographic analysis helped highlight areas of malaria risk and clarified ecologic risk factors for transmission. Remote sensing enabled development of a risk map, thereby providing a valuable tool to help guide malaria control strategies.